DECONSTRUCTION OF ‘PRIAYI” JAVANESE FAMILY PATRIARCHY ISSUE IN NOVEL CANTING BY ARSWENDO ATMOWILOTO - Neisya - (Politeknik Negeri Sriwijaya, 2016)
This research has the purpose to reveal the patriarchy culture happens in Javanese woman’s life pictured in novel Canting by ArswendoAtmowiloto. It then tries to reconstruct and reverse the inferiority image of Javanese woman in the novel who was described as domestic figure only became a woman that actually independent and had a power to rule her husband life. The researcher used deconstruction method to reverse the meaning which wants to be described by Arswendo. In novel Canting, the patriarchy construction of Priyayi Javanese woman was presented through the obedience of Bu Bei to her husband. She served every necessities of Pak Bei during her life. Through the deconstruction, the researcher was then able to reveal that actually Bu Bei was the person who had the superiority because without her, Pak Bei could do nothing, included for the preparation of Bu Bei’stahlilan (praying after the death). This research used feminism approach to describe the image of woman in Javanese patriarchy culture. Through the research, the readers would know the superiority of a woman through her fairness and womanity.